The Mediation Role of Employee Engagement in the Relationship Between Work-Life Balance, Psychological Empowerment, Leadership, and Meaningful Work Towards Turnover Intention (A Study of Female Employees of PT Telkom Infrastruktur Indonesia) - Putri, Ayu Adinda; Runing, Hunik Sri (Dinasti International Journal of Education Management and Social Science, 2025)
This study is a literature review that analyzes a model for increasing and decreasing turnover intention through a framework of strengthening employee engagement. This approach provides a theoretical contribution by applying Discrepancy Theory in the context of modern work behavior, particularly for female workers in dynamic industrial sectors, where the match between expectations and work reality is key to forming long-term loyalty and engagement. This study was conducted only for female employees. PT. Telkom Infrastruktur Indonesia, a married couple, totalling 121. This study uses Structural Equation Modelling (SEM) analysis, using AMOS, to determine whether the model depicted corresponds to actual reality. The results of this study indicate that work-life balance, psychological empowerment, leadership, and meaningful work have a positive impact on employee engagement. The better the work-life balance, psychological empowerment, leadership, and meaningful work, the better. This has the potential to strengthen female employees' attachment to the organization. In this study, work-life balance contributed significantly to increasing employee engagement. Employee engagement had a significant negative effect on turnover intention. In this study, stronger employee engagement potentially reduced female employees' desire to leave the organization.